Chiroptically-active metal oxide nanomaterials - CLEARY, OLAN (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2018)
The aim of this work was to develop and characterise a variety of new chiroptically-active metal oxide nanomaterials, with a view to exploring their potential enantioselective catalytic, biomedical, chiroptical applications. In this thesis, Chapter 1 presents a literature review of the areas relevant to this research and is a general introduction to the field chiroptically-active nanomaterials. Chapter 2 details the synthesis and characterisation of a chiral and luminescent TiO2 nanomaterials which have been prepared by a single step nonaqueous synthesis. These materials are then fully characterised by various instrumental techniques. These chiroptically-active TiO2 NPs were also tested for catalytic activity in a range of organic transformations. Chiral polymer templates made from a tartaric acid and PEI complex are used for the production of an amorphous, chiroptically-active TiO2 based nanomaterials. Finally, 16-2-16 gemini tartrates were also used for the preparation of chiral TiO2 with a helical morphology. In Chapter 3, a range of chiroptically-active Mn3O4 NPs were prepared through functionalisation with a variety of chiral ligands. The catalytic properties of the Mn3O4 NPs were also tested. The chiroptically-active Mn3O4 NPs were also tested for activity against against breast cancer cells. Finally, we report the synthesis and preliminary studies of a chiral metal organic framework (MOF) as a new chiral nanomaterial. Chapter 4 reports the development of chiroptically-active and luminescent ZnO NPs. The chiroptical and luminescent properties of these NPs are also characterised. Chapter 5 describes the development of a catalyst for both aldol and Michael reactions by ligand self assembly on the surface of CeO2 NPs. Chapter 6 describes all experimental details relating to the work presented in this thesis and has been labelled with the specific experimental details concerning the results in each chapter. Details of all instrumental techniques used in our work are also presented in this chapter. Chapter 7 provides the conclusions of the entire work and outlines the main achievements of our research. This chapter also includes details of future directions of our work.
APPROVED
Keywords: Chemistry; Nanomaterials; Metal Oxides; Luminescent; Chiroptically-Active; Catalysis